Implementasi triple helix of economic education terintegrasi sustainable develompent goals (SDGs) dalam konteks merdeka belajar kampus merdeka - Riril Mardiana Firdaus; Endah Andayani; Udik Yudiono; Walipah Walipah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
The objective of the Merdeka Belajar Kampus Merdeka policy is to encourage students to master various fields of knowledge with their fields of expertise. This policy provides an opportunity for students to choose the courses they will take based on their own wishes. The implementation of the Merdeka Belajar Kampus Merdeka policy encourages the learning process in higher education to be more autonomous and flexible. Not only highly educated but also able to become agents of change in small and large scope. The resulting changes and innovations are able to make a maximum contribution to the progress of a nation that has quality human resources. In general, this research is based on the principles of descriptive analytic/descriptive analysis. It is said to be analytical because in this research the point is to understand the extent to which the implementation of the Triple Helix Of Economic Education is integrated with the SDGs in the context of MBKM. The population in this study were all students of economic education at the Universitas PGRI Kanjuruhan Malang who had implemented MBKM, Economic Education Lecturers, Practitioners from the Economics MGMP Teacher Malang City and the Buring Village Government, Kedungkandang District as partners. From the results of the research that has been done, namely the implementation of the Triple Helix in the Economic Education Study Program that is integrated in a sustainable manner in the Merdeka Belajar Kampus Merdeka Context (MBKM), the results are quite satisfactory from the point of view of academics (lecturers), practitioners, and government institutions.